Particle Swarm Optimization and Differential Evolution for model-based object detection - Ugolotti, Roberto; Nashed, Youssef S.G.; Mesejo, Pablo; Ivekovič, Špela; Mussi, Luca; Cagnoni, Stefano (Applied soft computing, 2013)
[Display omitted] ► We present a very general model-based approach to object detection. ► This method can be applied to any kind of objects, as long as some invariant features can be used to define a model. ► We compare PSO and DE on two real-world problems: hippocampus localization and human body pose estimation. ► We parallelized the optimization techniques and the localization functions, for execution by GPU within the CUDA environment. Automatically detecting objects in images or video sequences is one of the most relevant and frequently tackled tasks in computer vision and pattern recognition. The starting point for this work is a very general model-based approach to object detection. The problem is turned into a global continuous optimization one: given a parametric model of the object to be detected within an image, a function is maximized, which represents the similarity between the model and a region of the image under investigation. In particular, in this work, the optimization problem is tackled using Particle Swarm Optimization (PSO) and Differential Evolution (DE). We compare the performances of these optimization techniques on two real-world paradigmatic problems, onto which many other real-world object detection problems can be mapped: hippocampus localization in histological images and human body pose estimation in video sequences. In the former, a 2D deformable model of a section of the hippocampus is fit to the corresponding region of a histological image, to accurately localize such a structure and analyze gene expression in specific sub-regions. In the latter, an articulated 3D model of a human body is matched against a set of images of a human performing some action, taken from different perspectives, to estimate the subject's posture in space. Given the significant computational burden imposed by this approach, we implemented PSO and DE as parallel algorithms within the nVIDIA™ CUDA computing architecture.